Validity of a Think Pair Share Based Student Worksheet (LKPD) for Grade XI Vocational High School Students - Elsa Putri Handayani; Refnywidialistuti Refnywidialistuti; Teni Suriani (The Future of Education Journal, 2026)
This study aims to develop an electronic Student Worksheet (LKPD) based on the cooperative Think-Pair-Share model that is valid and practical for mathematics learning among Phase F Fashion students at SMK Negeri 6 Padang. This study is motivated by the limited variety of teaching materials and the use of textbooks that do not fully guide students to learn independently, engage in discussions, and participate actively in the learning process. This research uses a development research method with a modified 4-D model limited to the develop stage. Data were collected through interviews, validation sheets, and response questionnaires from teachers and students, then analyzed quantitatively using a Likert scale. The developed LKPD follows the stages of think, pair, and share, and is expected to support mathematics learning that is more structured, engaging, active, and collaborative.The research results indicate that, regarding the student worksheet (LKPD) incorporating the TPS model, the calculated value for subject matter expert validation was 0.87 (very high), while the calculated value for language validation wes 0.12 (very high).